Analisis Kesalahan Berbahasa pada Tingkat Morfologi dalam Komentar Pengguna Internet di Unggahan Akun Tiktok @Fadiljaidi - Kusnanda, Dilla Dwi; Risnawaty, Risnawaty (Melati Institute, 2024)
This research aims to examine word usage errors, especially, prefixes and suffixes in netizen comments on @FadilJaidi's TikTok account. The type of research used is descriptive qualitative. The research data is in the form of comments in the TikTok @FadilJaidi account covering the period April to June 2024. The data collection technique uses the screen capture method and documentation using the read and record technique on the comments of internet citizens on the TikTok @FadilJaidi account uploads. The results of this study show that there are 30 errors consisting of 23 errors in the use of prefixes, namely: ngerasain, nemu, nyuci, ngetik, ngajak, keinget, dipake, ngisengin, ngepel, ngajarin, ngliat, nyari2, engeh, nyaut, nyulam, ngucapin, nyium, ngakuin, ngekonten, ngobrol, ngunyah, ngeh gandeng, ngusap. There are 7 errors in the use of suffixes, namely, ditambain, mengkaget, berangkatin, ngutang, add in, manjain, buatin. The findings show that incorrect word usage, especially prefixes and suffixes, is still rampant among netizens, especially on social media. It is hoped that this research can contribute to understanding the patterns of good and correct Indonesian language usage, especially in the context of conversations on social media.